A fundamental developmental transition in Physcomitrium patens is regulated by evolutionarily conserved mechanisms. Issue 3 (6th April 2021) - Jaeger, Richard; Moody, Laura A.
Abstract: One of the most defining moments in history was the colonization of land by plants approximately 470 million years ago. The transition from water to land was accompanied by significant changes in the plant body plan, from those than resembled filamentous representatives of the charophytes, the sister group to land plants, to those that were morphologically complex and capable of colonizing harsher habitats. The moss Physcomitrium patens (also known as Physcomitrella patens ) is an extant representative of the bryophytes, the earliest land plant lineage. The protonema of P. patens emerges from spores from a chloronemal initial cell, which can divide to self‐renew to produce filaments of chloronemal cells. A chloronemal initial cell can differentiate into a caulonemal initial cell, which can divide and self‐renew to produce filaments of caulonemal cells, which branch extensively and give rise to three‐dimensional shoots. The process by which a chloronemal initial cell differentiates into a caulonemal initial cell is tightly regulated by auxin‐induced remodeling of the actin cytoskeleton. Studies have revealed that the genetic mechanisms underpinning this transition also regulate tip growth and differentiation in diverse plant taxa. This review summarizes the known cellular and molecular mechanisms underpinning the chloronema to caulonema transition in P. patens . Abstract : A proposed model for the chloronema to caulonema transition in P. patens. The differentiation of caulonemata is dependent on the auxin‐induced remodelling of the actin cytoskeleton, but is also underpinned by complex hormone crosstalk that overlaps with light and sugar signaling pathways.